Peculiarities of specular infrared reflection spectra of ZnO-based ceramics - Melnichuk, O.V.; Korsunska, N.O.; Markevich, I.V.; Boyko, V.V.; Polishchuk, Yu.O.; Tsybrii, Z.F.; Melnichuk, L.Yu.; Venger, Ye.F.; Kladko, V.P.; Khomenkova, L.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Undoped and Mn-doped ZnO ceramics were theoretically and experimentally investigated using the specular infrared reflection method. It was shown that infrared reflection spectra can be modeled using the parameters explored for ZnO single crystals. For ceramic samples, it was shown that ZnO grains with the orientation of the -axis along the normal to the electric field ( ⃗ ⊥ ) give the main contribution to IR reflection spectra. It has been ascertained that the surface roughness is manifested in these spectra mainly within the range 450…550 cm⁻¹, giving a negligible effect for the frequencies above the longitudinal phonon frequency. This allowed the electrophysical parameters of ZnO crystallites to be evaluated. In the case of undoped ceramics, the obtained results were found to be consistent with the values of direct current measurements. This finding supports the utility of infrared spectroscopy for the determination of the electrophysical parameters of polycrystalline ceramic materials. For Mn-doped ceramic samples, the conductivity value measured using the direct current method was found to be essentially lower than that determined from the simulation of infrared reflection spectra. This phenomenon was explained by barrier formation at the grain boundaries in Mn-doped ZnO ceramics. Виготовлено нелеговану та леговану манганом кераміку оксиду цинку та досліджено її структурні, оптичні та електричні властивості. Показано, що метод інфрачервоної спектроскопії може бути застосований для визначення електрофізичних параметрів керамічних зразків. При цьому для моделювання спектрів інфрачервоного відбивання таких зразків можна використовувати параметри, одержані для монокристалів ZnO. Виявлено, що основний внесок у спектри інфрачервоного відбивання керамічних зразків надають зерна ZnO з орієнтацією осі , перпендикулярної до напрямку вектора електричного поля (⃗⊥). Установлено, що шорсткість поверхні проявляється в цих спектрах переважно в діапазоні 450–550 см⁻¹, що дає незначний ефект у діапазоні частот вищих за частоту LO-фонона. Проведено оцінку електрофізичних параметрів нелегованих та легованих манганом зразків. Установлено, що у разі нелегованої кераміки отримані результати збігаються з результатами прямих вимірювань електропровідності зразків. Для керамічних зразків, легованих манганом, пряме вимірювання їх провідності дає значення, яке значно менше за величину, одержану при моделюванні спектрів інфрачервоного відбивання. Така відмінність пояснюється утворенням бар’єрів на границях зерен ZnO, легованих манганом.